Congenital cholesteatoma of middle ear: clinical features and surgical outcomes - Solanki, Karnadev J.; Nakum, Nikunj N.; Mehta, Muskan V. (International Journal of Research in Medical Sciences, 2026)
Congenital cholesteatoma of the middle ear is an uncommon entity, often detected incidentally in children. The present case series evaluates the clinical presentation and surgical outcomes of patients with congenital cholesteatoma. Ten patients diagnosed with congenital cholesteatoma underwent surgical eradication of the disease. Postoperative cavity status and hearing outcomes were assessed at a 3-month follow-up using pure tone audiometry, and air–bone gaps were calculated. The mean preoperative air–bone gap was 54.50±14.62 dB, which improved to 35.50±11.41 dB postoperatively, demonstrating a mean hearing gain of 19.00 ± 5.68 dB. Histopathological examination confirmed the diagnosis of cholesteatoma in all cases. No recurrence was observed during the follow-up period. Early diagnosis based on micro-otoscopy, supported by computed tomography of the temporal bone, and complete surgical excision provide satisfactory anatomical and audiological outcomes in congenital cholesteatoma.